The yeast G-protein homolog is involved in the mating pheromone signal transduction system. - Fujimura, H A (1989)
I have isolated a new type of sterile mutant of Saccharomyces cerevisiae, carrying a single mutant allele, designated dac1, which was mapped near the centromere on chromosome VIII. The dac1 mutation caused specific defects in the pheromone responsiveness of both a and alpha cells and did not seem to be associated with any pleiotropic phenotypes. Thus, in contrast to the ste4, ste5, ste7, ste11, and ste12 mutations, the dac1 mutation had no significant effect on such constitutive functions of haploid cells as pheromone production and alpha-factor destruction. The characteristics of this phenotype suggest that the DAC1 gene encodes a component of the pheromone response pathway common to both a and alpha cells. Introduction of the GPA1 gene encoding an S. cerevisiae homolog of the alpha subunit of mammalian guanine nucleotide-binding regulatory proteins (G proteins) into sterile dac1 mutants resulted in restoration of pheromone responsiveness and mating competence to both a and alpha cells. These results suggest that the dac1 mutation is an allele of the GPA1 gene and thus provide genetic evidence that the yeast G protein homolog is directly involved in the mating pheromone signal transduction pathway.